Stroke in young adults: a prospective study of 58 patients - Gomes, Ana (2008)
Introduction and aims: Stroke in young adults is less frequent and has a wider variety of causes, requiring more extensive investigation. Our aim was to evaluate the demographics, stroke type, risk factors, outcome and mortality in patients younger than 60 years.Methods: Prospective study lasting 2 years (2002- 2003) of all patients aged under 60, admitted with stroke, to our department. Patients with subarachnoid haemorrhage were excluded. The study protocol included history, physical examination, computed tomography (CT), ECG, transthoracic cardiac ultrasound, carotid Doppler, blood analysis for pro-clotting and atherogenic factors and a 6-month follow-up. Other studies were performed when deemed necessary. Results: We studied 58 patients, 30 women (51.7%) and 28 men (48.3%) aged 32 to 60 (mean age 51.9±6,3). The majority (77.6%) had ischaemic stroke, 20% had haemorrhagic stroke and one patient had thrombosis of the venous sinus. The main risk factors for ischaemic stroke were hypertension (66.7%) and hyperlipidemia (64.4%); and for hemorrhagic stroke hypertension (75%) and alcoholism (58.3%). The overall mortality was 13.8%. Only 43.1% of all patients recovered without sequelae.Conclusions: Besides age, the classic risk factors for atherosclerosis were the main risk factors identifiable, although alcoholism was the second risk factor for haemorrhagic stroke. The high percentage of mortality and disability associated with stroke underlines the absolute need to control these risk factors in the population.